Framework Considerations for Rural Resilience Toward Land Degradation - Rahmawati, Isna; Rudiarto, Iwan (KnE Social Sciences, 2019)
Landdegradationisaglobalproblemwhichinvolvesclimate,soil,vegetation,economic, andpopulationconditions.Landdegradationoccursinruralagriculturallandasaresult of agricultural activities. Land degradation can ultimately eliminate the sustainability of environmental, social and economic in rural areas. Land degradation problems decline environmental, social and economic conditions that decrease rural resilience. Basically the components of community resilience according to Kusumastuti [14] can be used to assesstheresilienceofruralcommunitiesbecausetheyinvolvenotonlyenvironmental, social and economic aspects but also community cappacity, institutions, infrastructure and hazards. Varoius studies were still involve environmental, social and economic. Keywords: rural resilience; vulnerability; preparedness; land degradation.